2021
DOI: 10.1089/bfm.2020.0308
|View full text |Cite
|
Sign up to set email alerts
|

#EveryGenerationMatters: Intergenerational Perceptions of Infant Feeding Information and Communication Among African American Women

Abstract: Objective: African American (AA) women look to their mother and maternal grandmother for parenting information and support; this intergenerational communication may reinforce or hinder breastfeeding practices. Rooted in Black Feminist Thought, this study's objective was to use an asset-based approach to explore infant feeding information shared across at least two generations of AA female family members. Materials and Methods: Fifteen family triads/dyads (N = 35 women), residing in Southeastern United States, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Previous research has identified that early introduction of solids as well as adding cereal to the bottle early in an infant’s life are considered cultural norms for African American mothers [ 28 ], but it is not yet well understood why this is the case. In qualitative studies, African American mothers have reported adding cereal to their infant’s bottle to help them sleep through the night [ 29 , 36 ]. Previous work has also highlighted the prominence of intergenerational influences on African American mothers’ bottle-feeding practices [ 28 , 36 ], suggesting that these behaviors may be entrenched and difficult to change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has identified that early introduction of solids as well as adding cereal to the bottle early in an infant’s life are considered cultural norms for African American mothers [ 28 ], but it is not yet well understood why this is the case. In qualitative studies, African American mothers have reported adding cereal to their infant’s bottle to help them sleep through the night [ 29 , 36 ]. Previous work has also highlighted the prominence of intergenerational influences on African American mothers’ bottle-feeding practices [ 28 , 36 ], suggesting that these behaviors may be entrenched and difficult to change.…”
Section: Discussionmentioning
confidence: 99%
“…In qualitative studies, African American mothers have reported adding cereal to their infant’s bottle to help them sleep through the night [ 29 , 36 ]. Previous work has also highlighted the prominence of intergenerational influences on African American mothers’ bottle-feeding practices [ 28 , 36 ], suggesting that these behaviors may be entrenched and difficult to change. Other research has indicated that low-income mothers often receive messages from their social networks that conflict with infant feeding recommendations [ 37 ] and that low-income mothers may perceive that infant feeding recommendations do not fit with their family’s needs [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is opportunity here to ask more sophisticated, socially‐grounded, anti‐racist questions about growth in the U.S. The use of Black‐centered theory (such as Black Feminist Thought) and asset‐based approaches have been used successfully in breastfeeding research (Woods Barr et al, 2021) and would be a valuable addition to U.S. growth studies.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to white women who relied on intrapersonal factors (e.g., breastfeeding attitudes and knowledge) and Latina women who relied on environmental factors (e.g., behavioral control with pump availability) to breastfeed, Black women valued subjective norms (e.g., opinions of family and friends) when making breastfeeding decisions (Bai et al, 2011). Attending to familial and community beliefs highlighted an Afrocentric norm of collectivism (Woods Barr, Miller, et al, 2021. In Woods Barr, Austin, et al (2021), Black families’ histories of breastfeeding were influential for mothers’ breastfeeding decisions to initiate and sustain the practice.…”
Section: Introductionmentioning
confidence: 99%